Developing a novel device, Eggcell, to improve temperature stability during oocyte collection for IVF. Issue 6 (December 2022) - Prathalingam, Nilendran; Hyslop, Louise; Cole, Michael; Cooney, Daniel; Driver, Alex; Herbert, Mary; Hodgson, Robert; Choudhary, Meenakshi; Wetherall, Ben; Shivhare, Sourima; Richardson, Jessica; Smith, Tom; et al.
Highlights: Standard oocyte collection procedures result in significant cooling This cooling is primarily related to loss of latent heat of evaporation Collection into an air-tight fluid container improves temperature stability Abstract: Research question: What temperature fluctuations are oocytes exposed to during oocyte retrieval? Can an alternative method of oocyte retrieval be designed to minimize these fluctuations? Design: Mock oocyte retrieval procedures were performed to investigate the change in temperature when the follicular fluid is drained into collection tubes and when the fluid is subsequently poured into dishes to allow identification of the cumulus–oocyte complex (COC). A new device, the Eggcell, has been designed that addresses the problem of these temperature fluctuations. To confirm its safety and demonstrate the clinical applicability of Eggcell, laboratory validation was performed prior to use with human participants ( n = 15). Results: Eggcell meets its design specification to provide temperature stability within the physiological range for aspirated follicular fluid. The COC can be successfully retained within the chamber ( n = 180) without evidence of loss or damage to the oocytes or compromise of fertilization rate, blastocyst development or clinical outcome. Conclusions: This study has demonstrated the successful first stages of development of a new medical device. Further studies are needed for comparative evaluation of clinical outcome with standard technology.